ANALISIS KELAYAKAN FINANSIAL UPAYA MENINGKATKAN PENDAPATAN PRODUSEN STROBERI SELAMA PANDEMI COVID 19 DI MAGELANG JAWA TENGAH - Prima Gandhi; Wawan Oktariza; Muhammad Kahfi; Annisa Rizky (Journal of Management Small and Medium Enterprises (SMEs), 2022)
Horticultural agribusiness such as fruits has local and international market share. Besides that, Fruit agribusiness supports the eighth Sustainable Development Goals (SDGs). One of the fruits that have become a commodity for agribusiness in Indonesia is the strawberry. Magelang Regency is a regency in Indonesia that produces strawberries. SOGA Farm Indonesia (SFI) located in Ngablak District is a strawberry producer that fulfills the demand for strawberries in Magelang Regency. To meet the demand for strawberries to income, SFI regulates the cropping pattern with a single row plant system to produce grade A strawberries and processes strawberries of below standard quality into strawberry jam. To determine financial feasibility, it is done by calculating the Net Present Value (NPV), Gross B/C, Net B/C, Internal Rate of Return (IRR), and Payback Period. The financial analysis results of these two businesses are feasible to increase SFI's income during the Covid 19 pandemic. Keywords: Income, Productivity, SDGs, Jam, Single Row Plant